New species and new distributional records of Elanela Rolston, 1980 (Heteroptera: Pentatomidae) - de Barros, Lurdiana Dayse; Barão, Kim Ribeiro; Grazia, Jocelia (Zootaxa, 2020)
Two new species are described, Elanela colombiana sp. nov. from Colombia, with disk of scutellum callused, ivory and abdominal sternite VIII immaculate medially, and Elanela ecuatoriana sp. nov., from Ecuador, distinguished by legs with black spots and the dorsal rim and ventral rim of pygophore with a medial process. Illustrations of habitus and genitalia of each species are provided and the distributional map was updated to include the new species and a new record of E. jordi. Additionally, the identification key to the species of Elanela is updated to include the new species.